ANALISIS PENGARUH PANDEMI COVID-19 TERHADAP PELAYANAN KESEHATAN DASAR DI PUSKESMAS KEPIL 1 KABUPATEN WONOSOBO JAWA TENGAH - tasyrifah, ghina mutiara (JURNAL SMART ANKes, 2025)
Covid-19 has attacked the world since the end of 2019 until now, one of which is Indonesia which has a significant impact on essential health services in 90% of countries where when COVID-19 becomes something terrible for people when sick, they are afraid to come. health services because of concerns about being diagnosed with COVID-19 positive. Many mitigations have been carried out to maintain the quality of health services, but the results are still negative. Patient visits at the Kepil 1 Health Centerin 2020 - 2021 have decreased quite drastically.This study aims to determine and further analyze the effects of the COVID-19 pandemic on basic health services at the Kepil 1 Health Center, Wonosobo Regency. Qualitative research with phenomenological research design. Use triangulation of sources and data, namely observation, document review, and in-depth interviews with question guidelines. Informants were selected by snowball sampling. In this study, it was found that the influence of the covid-19 pandemic contained findings in the input, process and output of the health care system of the Kepil 1 Public Health Center which resulted in a decrease in the number of patient visits.The analysis of the COVID-19 pandemic on basic health services at the Kepil 1 Public Health Center found new findings in the input, process, and output. In overcoming these findings, it can be overcome by maintaining the system that is already good and improving the system that is still lacking. Suggestion: Public health centercan maintain time efficiency during examinations, maintain services involving technology, maintain innovation in online service patterns even though the pandemic has passed, maintain quality assurance service patterns for the community, add health workers and maintain training.